Déprises et réagencement de la maternité. Regards sur les expériences de femmes ayant fait placer leurs enfants - Jessica Pothet (Genre, Sexualité et Société)
Starting from a survey through interview with mothers who are in a “single parent” situation and a social vulnerability situation, this article is questioning under a gender angle, maternity through its abandon. The article enlightens an absence of social dual-parenthood, especially anchored in the precarious pole of working classes, and shows that the disengagement of the father combined to a social and relational precarity may participate in a redefinition of maternity. The enquiry shows us two important elements, on one hand, it shows how this maternal role under tension can renew itself far away from norms of maternal devotion, as we can see with the women interrogated who choose to place their children in social services and on the other hand, it shows how a relationship of desire and an affective, emotional relationship can be rebuilt after that.